2020
DOI: 10.1101/2020.07.08.193763
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Alpha/beta power decreases during episodic memory formation predict the magnitude of alpha/beta power decreases during subsequent retrieval

Abstract: AbstractEpisodic memory retrieval is characterised by the vivid reinstatement of information about a personally-experienced event. Growing evidence suggests that the reinstatement of such information is supported by reductions in the spectral power of alpha/beta activity. Given that the amount of information that can be recalled depends on the amount of information that was originally encoded, information-based accounts of alpha/beta activity would suggest that retrieval-relate… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…Moreover, interfering with these power decreases via transcranial magnetic brain stimulation impairs episodic memory formation . Together, these findings (see also Fellner et al, 2013;Griffiths et al, 2021;Karlsson et al, 2020;Long & Kahana, 2015;Martín-Buro et al, 2020;Sederberg et al, 2007) suggest that alpha/beta power decreases are intimately tied to the successful representation of information pertaining to episodic memories.…”
Section: Introductionmentioning
confidence: 89%
“…Moreover, interfering with these power decreases via transcranial magnetic brain stimulation impairs episodic memory formation . Together, these findings (see also Fellner et al, 2013;Griffiths et al, 2021;Karlsson et al, 2020;Long & Kahana, 2015;Martín-Buro et al, 2020;Sederberg et al, 2007) suggest that alpha/beta power decreases are intimately tied to the successful representation of information pertaining to episodic memories.…”
Section: Introductionmentioning
confidence: 89%
“…Indeed, while it appears likely that the effect reflects some form of memory reactivation, it is unclear whether this reactivation reflects context retrieval, as is suggested by the two-factor framework (Bäuml, 2019), or reactivation of the restudied items themselves. In the literature, (parietal) alpha power decrease has been suggested to be positively related to memory reactivation in both short-term (Klimesch et al, 2005) and long-term memory tasks (Griffiths et al, 2021;Martín-Buro et al, 2020). For instance, Martín-Buro et al (2020) examined alpha power decrease during recognition testing and found that left posterior alpha power decrease was positively related to both item recognition and associative recall.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Martín-Buro et al (2020) examined alpha power decrease during recognition testing and found that left posterior alpha power decrease was positively related to both item recognition and associative recall. Griffiths et al (2021) examined alpha/beta power decrease with recall testing and argued that alpha/beta power decrease may be unrelated to the reactivation of stimulus-specific information but related to "supportive processes" that accompany the encoding and retrieval of episodic memories.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations